2006
DOI: 10.1016/j.socscimed.2006.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Racism and health: The relationship between experience of racial discrimination and health in New Zealand

Abstract: Accumulating research suggests that racism may be a major determinant of health. Here we report associations between self-reported experience of racial discrimination and health in New Zealand. Data from the 2002/2003 New Zealand Health Survey, a cross-sectional survey involving face-to-face interviews with 12,500 people, were analysed. Five items were included to capture racial discrimination in two dimensions: experience of ethnically motivated attack (physical or verbal), or unfair treatment because of ethn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
248
3
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 302 publications
(269 citation statements)
references
References 43 publications
13
248
3
2
Order By: Relevance
“…These findings are in line with several reviews and studies that have consistently suggested that experienced discrimination has a harmful psychological impact on those against whom it is directed (e.g., Brondolo et al, 2009b;Harrell, 2000;Harris et al, 2006: Krieger, 1999Paradies, 2006;Priest et al, 2012;Williams & Mohammed, 2009;2013a;2013b).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…These findings are in line with several reviews and studies that have consistently suggested that experienced discrimination has a harmful psychological impact on those against whom it is directed (e.g., Brondolo et al, 2009b;Harrell, 2000;Harris et al, 2006: Krieger, 1999Paradies, 2006;Priest et al, 2012;Williams & Mohammed, 2009;2013a;2013b).…”
Section: Discussionsupporting
confidence: 90%
“…Racial and ethnic discrimination has also been seen as affecting physical health through negative health behaviors, because several studies have consistently shown the relationship between perceived racial/ethnic discrimination and risky behaviors such as smoking and substance abuse (e.g., Borrell et al, 2010;Harris et al, 2006;Landrine & Klonoff, 1996).…”
Section: Racial/ethnic Discrimination and Psychological Well-beingmentioning
confidence: 99%
“…There are disparities in rates of mental health needs across specific ethnic groups, depending on age and the particular measures used. The specific needs of ethnic minority youth are sometimes overlooked due to racism and other barriers 12,13 . Māori and Pacific youth report higher rates of suicidality, violence, and use of substances than NZ European youth 14,15 .…”
Section: Introductionmentioning
confidence: 99%
“…However, if the policy goal at national level is to reduce ethnic inequalities in health, then the focus of policy (e.g. funding formulae) needs to be on factors directly linked to ethnicity, such as socio-economic deprivation and other manifestations of discrimination, [8][9][10] rather than on geographic variations in health and health care that have an impact on all ethnic groups more-or-less alike.…”
Section: Discussionmentioning
confidence: 99%